Complex Analyses of Plankton Structure and Function - Karl E. Havens (The Scientific World Journal)
This paper critically evaluates some complex methods that have been used to characterize the structure and function of freshwater plankton communities. The focus is on methods related to plankton size structure and carbon transfer. The specific methods reviewed are 1) size spectrum analysis, 2) size-fractionated phytoplankton productivity, 3) size-fractionated zooplankton grazing, 4) plankton ecological transfer efficiency, and 5) grazer effects on phytoplankton community structure. Taken together, these methods can provide information on community ecological properties that are directly related to practical issues including water quality and fisheries productivity. However, caution is warranted since application without a complete understanding of assumptions and context of the manipulations could lead to erroneous conclusions. As an example, experimental studies involving the addition or removal of zooplankton, especially when coupled with nutrient addition treatments, could provide information on the degree of consumer vs. resource control of phytoplankton. Resource managers subsequently could use this information in developing effective measures for controlling nuisance algal biomass. However, the experiments must be done critically and with sufficient safeguards and other measurements to ensure that treatments (e.g., zooplankton exclosure by screening of water) actually are successful and do not introduce other changes in the community (e.g., removal of large algae). In all of the methods described here, the investigator must take care when generalizing results and, in particular, carry out a sufficient number of replications to encompass both the major seasonal and spatial variation that occurs in the ecosystem.